Data Sanitization Evaluation in Donated Computers During the COVID-19 Pandemic: A Case Study at IFSP Hortolândia - Oliveira, Arthur de; Sambinelli, Fernando (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais Estendidos do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2024)
This study evaluates the effectiveness of data sanitization procedures on IT equipment donated to the Federal Institute of São Paulo (IFSP) Hortolândia campus during the COVID-19 pandemic. Using forensic computing techniques, some donated computers were examined, revealing the presence of sensitive personal data belonging to public servants from the donor agencies. This discovery highlights a significant failure in the data sanitization process conducted by the federal donor agency, emphasizing the urgent need for compliance with Brazilian regulations such as Normative Instruction No. 01/2010 and the General Data Protection Law (LGPD - Lei Geral de Proteção de Dados Pessoais). The study underscores the importance of adopting rigorous data sanitization practices, providing continuous training to staff, and conducting regular audits to ensure the security and privacy of information in public agencies.